Can oral history improve healthcare professionals understanding of patients in palliative care?. Issue 2 (1st September 2011) - Winslow, Michelle; Smith, Sam; Noble, Bill
Abstract : This presentation will consider the potential benefit of oral history in the context of medical and nurse education to aid a deeper understanding between patient and physician. We contend that oral history is a valid source of information for use in educating healthcare professionals through the reproduction of the authentic voice of the interviewee. An oral history is a deeply personal account that expresses identity and explores meaning. When heard together with a clinical history there is potential for health professionals to gain knowledge of the variety of patients' experiences, deepening and broadening awareness of the process and consequences of disease. This understanding can enhance awareness of psychosocial matters and prepare them for clinical encounters in the future. In palliative care, health professionals hear the concerns and distress of individual patients and carers by a process of active listening and structured questioning; their knowledge is synthesised from findings arising from population case studies and studies using both quantitative and qualitative methodologies. While oral history makes no claim to be generalisable in a scientific sense, like other practices in the humanities, it does seek to describe the human condition. Oral histories are uncluttered by imposed theoretical frameworks or extrinsic interpretations and in this sense the patient has greater agency and the health professional can gain more rounded understandings. The value of oral history to the health professional is that it allows communication with patients and carers that is unfiltered by a medical agenda. Accounts of patients' experience are put into context in a way that retains their individual voice and agency.